Pengembangan Bahan Ajar Fiqih Lingkungan berbasis Socio-Eco-Techno-Preneurship di Institut Agama Islam Negeri Metro - Mahmudah, Nurul; saputera, Abdur Rahman adi; Alkautsar, Muhammad Syakir (Tapis: Jurnal Penelitian Ilmiah, 2020)
The lack of references to Environmental Fiqh teaching materials at IAIN Metro is an obstacle for lecturers to deliver an understanding for the students for the taught subject. This research was conducted to develop environmental Fiqh teaching materials as well as support the vision and mission of the State Islamic Institute of Metro in educating the academic community so that students understand how to manage the environment in accordance with Islamic principles to support socio-eco-techno-preneurship. The results of this study were carried out by exploring the strengths and weaknesses, collecting data, and formulating teaching materials adapted from Borg and Gall. The steps taken are compiling the initial product format, revising the product, field testing, revising the final product based on the evaluation of expert judgment, and ending with dissemination.